Development of a subset of the international classification of functioning, disability and health as a basis for a questionnaire for community-dwelling older adults aged 75 and above in primary care: a consensus study - Rink, Laura; Tomandl, Johanna; Womser, Sonja; Kühlein, Thomas; Sebastiao, Maria (BMJ Open, 2023)
Objectives Functioning of older adults needs to be adequately described before it can become the focus of care. The International Classification of Functioning, Disability and Health (ICF) provides a basis for describing functioning. As the ICF is too extensive for daily practice in primary care, there is a need for a reduced number of categories. The aim is to develop an ICF-subset for community-dwelling older adults aged 75 and above in primary care. Design The scientific basis for decision-making in our consensus study was laid by four preparatory studies, identifying potentially relevant ICF categories from four perspectives (research, patients', experts' and clinical perspective). The results of the preparatory phase were discussed by an international expert panel in a consensus study following the Nominal Group Technique (NGT). Setting An international 1-day online consensus conference. Participants International experts (n=7) participated in the consensus conference, meeting the following criteria: extensive expertise in the field of the ICF and/or caring for older adults, and being fluent in English. Results Each preparatory study yielded a different number of categories with some overlaps but also differences. The expert panel decided to: (1) restrict the subset to second-level categories and reduce the number of categories from the preparatory phase, (2) limit the subset to the component activities and participation and (3) weight the patients' perspective as the most relevant one. Conclusions By using consensus techniques and the NGT, the process led to 51 second-level ICF categories to describe the functioning of community-dwelling older adults. The decisions made in the consensus conference emphasised the importance of considering the individual life situation from a more holistic perspective and addressing functioning as a focus of care. Next, the 51 categories will contribute to the development of an ICF-based questionnaire.
CRIS-Team Scopus Importer:2023-09-15
Keywords: decision making; geriatric medicine; primary care; qualitative research